2005
DOI: 10.1590/s0103-50532005000600009
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rosuvastatin in human plasma by HLPC tandem mass spectroscopic method and its application to bioequivalence study

Abstract: Um método empregando LC-MS/MS foi desenvolvido para a análise de rosuvastatina em plasma humano, usando atorvastatina como padrão interno. Rosuvastatina é um fármaco para redução de lipídeos e prescrita para o tratamento do hipercolesterolemia e de dislipidimia. A extração em fase sólida (SPE) foi usada para purificação e pré-concentração do analito a partir da matriz do plasma humano. A separação cromatográfica foi conseguida em 6.0 min empregando fase móvel composta de 0.2% de ácido fórmico em água e acetoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Hull et al reported an automated solid phase extraction [14] which was successfully applied to a series of clinical trials on bioavailability, pharmacokinetic and metabolic [15] study of rosuvastatin. A similar method employing solid phase extraction and HPLC-MS/MS with a relative higher LLOQ of 1 ng mL −1 was recently reported by Singh et al [16]. Recently, a microbore HPLC in combination with tandem MS which was cross-validated to provide similar information on the concentration of rosuvastatin exhibited an ability of greatly reduced sample consumption [17].…”
Section: Introductionmentioning
confidence: 80%
“…Hull et al reported an automated solid phase extraction [14] which was successfully applied to a series of clinical trials on bioavailability, pharmacokinetic and metabolic [15] study of rosuvastatin. A similar method employing solid phase extraction and HPLC-MS/MS with a relative higher LLOQ of 1 ng mL −1 was recently reported by Singh et al [16]. Recently, a microbore HPLC in combination with tandem MS which was cross-validated to provide similar information on the concentration of rosuvastatin exhibited an ability of greatly reduced sample consumption [17].…”
Section: Introductionmentioning
confidence: 80%
“…Several methods based on different techniques have been reported for the analysis of PS, FVS, ATC, and RC in biological fluids. These include high-performance liquid chromatography-mass spectrometry (HPLC=MS) (Gao et al 2007;Lan et al 2007;Borek-Dohalsky et al 2006;Di Pietro et al 2006;Nirogi et al 2006;Oudhoff et al 2006;Xu et al 2006;Hermann, Christensen, and Reubsaet 2005;Singh et al 2005;Trivedi 2005;Zhu and Neirinck 2003) and HPLC (Bahrami et al 2005;Kumar et al 2006;Vittal et al 2006;Um et al 2005;Bauer et al 2005;Zarghi et al 2005;Altuntas and Erk 2004;Al-Rawithi, Hussein, and Alzahrani 2003). Although these methods are sensitive enough to permit their use in determination of PS, FV, ATC, and RC in urine, plasma, and serum, few methods are reported for assay of statins in pharmaceuticals.…”
Section: Development and Validation Of Stability-indicating Hplc Methmentioning
confidence: 99%
“…Common dosage forms are tablets and capsule (Ahmad et al, 2012). As per literature survey it reveals that, only few analytical techniques have been developed for the estimation of rosuvastatin calcium in bulk and pharmaceuticals such as High performance thin layer chromatography (HPTLC) method (Uma Devi et al, 2011), one Reverse phase high performance liquid chromatographic (RP-HPLC) method (Pandya et al, 2010) and few LC-MS methods (Singh et al, 2005). In this study an attempt was made to develop a simple spectrophotometric method for the estimation of the present drug in dosage form.…”
Section: Introductionmentioning
confidence: 99%